Internal Illumination to Overcome the Cell Density Limitation in the Scale-up of Whole-Cell Photobiocatalysis - Hobisch, Markus; Spasic, Jelena; Malihan-Yap, Lenny; Barone, Giovanni Davide; Castiglione, Kathrin; Tamagnini, Paula; Kara, Selin; Kourist, Robert (Chemsuschem, 2021)
Cyanobacteria have the capacity to use photosynthesis to fuel their metabolism, which makes them highly promising production systems for the sustainable production of chemicals. Yet, their dependency on visible light limits the cell-density, which is a challenge for the scale-up. Here, it was shown with the example of a light-dependent biotransformation that internal illumination in a bubble column reactor equipped with wireless light emitters (WLEs) could overcome this limitation. Cells of the cyanobacterium Synechocystis sp. PCC 6803 expressing the gene of the ene-reductase YqjM were used for the reduction of 2-methylmaleimide to (R)-2-methylsuccinimide with high optical purity (>99 % ee). Compared to external source of light, illumination by floating wireless light emitters allowed a more than two-fold rate increase. Under optimized conditions, product formation rates up to 3.7 mm h−1 and specific activities of up to 65.5 U gDCW−1 were obtained, allowing the reduction of 40 mm 2-methylmaleimide with 650 mg isolated enantiopure product (73 % yield). The results demonstrate the principle of internal illumination as a means to overcome the intrinsic cell density limitation of cyanobacterial biotransformations, obtaining high reaction rates in a scalable photobioreactor.
CRIS-Team Scopus Importer:2021-07-16
Keywords: asymmetric catalysis; biocatalysis; cyanobacteria; ene-reduction; photocatalysis